Passive RFID tag for biomass tracking and monitoring of temperature and humidity level - Ali, Amjad (2024)
The last few decades have seen the United Kingdom (UK) being strongly supportive of renewable energy (RE) resources to reduce the use of depleting fossil fuels and its resultant greenhouse gas (GHG) emissions. For this purpose, one of the strategies is to utilise biomass energy as an alternate source of fossil fuel in various sectors such as house heating, electric power generation and industrial usage. In order to use biomass in all these sectors, it is crucial to monitor local humidity and temperature levels to ensure quality, reduce the self-ignition risk and enable supply chain tracking. Some of these important parameters are currently monitored at a very high cost with the use of expensive and complicated battery-based devices. Due to fire risks, sensors cannot have batteries, and it is difficult to recover sensors before combustion. Thus, any whole life monitoring system must minimise the risk of fire, not pose a blocking hazard, and be combustible while also being low-cost to produce. To date, no such sensor tag has been demonstrated.